The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1155/2020/5973082
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Three-miRNA Signature Identified Using Bioinformatics Predicts Survival in Esophageal Carcinoma

Abstract: Objective. We identified differentially expressed microRNAs (DEMs) between esophageal carcinoma (ESCA) tissues and normal esophageal tissues. We then constructed a novel three-miRNA signature to predict the prognosis of ESCA patients using bioinformatics analysis. Materials and Methods. We combined two microarray profiling datasets from the Gene Expression Omnibus (GEO) database and RNA-seq datasets from the Cancer Genome Atlas (TCGA) database to analyze DEMs in ESCA. The clinical data from 168 ESCA patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 36 publications
(36 reference statements)
0
11
0
Order By: Relevance
“…Over-expression of hsa-miR-1301-3p induces cell proliferation and tumorigenesis in gastric cancer tissues [59] . Wu et al reported the differential expression of hsa-miR-1301-3p in ESCA, suggesting that this miRNA could be used as a prognostic biomarker for ESCA [60] . Zhang and colleagues reported the downregulation of hsa-miR-532-5p in gastric cancer cells, and its expression is associated with poorer survival in patients with gastric cancer [61] .…”
Section: Resultsmentioning
confidence: 99%
“…Over-expression of hsa-miR-1301-3p induces cell proliferation and tumorigenesis in gastric cancer tissues [59] . Wu et al reported the differential expression of hsa-miR-1301-3p in ESCA, suggesting that this miRNA could be used as a prognostic biomarker for ESCA [60] . Zhang and colleagues reported the downregulation of hsa-miR-532-5p in gastric cancer cells, and its expression is associated with poorer survival in patients with gastric cancer [61] .…”
Section: Resultsmentioning
confidence: 99%
“…A few previous studies have stratified subtypes of ESCC based on genomic profiling ( 7 9 , 39 ). However, the stratification of ESCC by immune signatures is poorly studied.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has aimed to uncover biomarkers with early diagnostic and prognostic value against EC. A 3-miRNA signature (miR-1301-3p, miR-769-5p, and miR-431-5p) has been suggested as a novel prognostic biomarker for EC ( 7 ). Li et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence has been increasing that abnormal miRNAs expression is involved in the pathogenesis and development of many cancers, which suggests the promising biomarkers for early diagnosis and therapy of tumors [5,10]. Now, a high-throughput platform combined with bioinformatics analysis has become a new way to identify biomarkers of disease [11,12].…”
Section: Introductionmentioning
confidence: 99%